EVALUACIÓN DE UNA VACUNA CONTRA Corynebacterium pseudotuberculosis EN RATONES ALBINOS - Medrano G., Giuliana (2003)
The granulomatous lymphadenitis is an economically important infectious disease in alpacas. This disease is caused by Corynebacterium pseudotuberculosis, which is a gram positive bacterium that has an exotoxin (Phospholipase D) as its main virulence factor. The objective of this study was to test the efficacy of a vaccine in a group of mice (20 vaccinated and 20 control). The vaccine was prepared with protein extracts from C. pseudotuberculosis isolated from an alpaca, containing the exotoxin, and used for the immunization of mice which received 16 g of protein extract. This confered protection after challenging intraperitoneally with 104 UFC of C. pseudotuberculosis. The vaccine ameliorated the toxic effects of C. pseudotuberculosis, which was evidenced by the decrease in number and size of abscesses in the vaccinated group (40% affected), in contrast with the severe and systemic damages found in the control animals (95% affected). Furthermore, a PCR methodology was set up in order to detect C. pseudotuberculosis in the experimental animals which showed abscesses, producing a band of 815 bp, indicating that C. pseudotuberculosis was the pathogen agent involved in the infections.